Characterization of a Novel POU1F1 Mutation Identified on Screening 160 Growth Hormone Deficiency Patients - Birla, Shweta; Vijayakumar, P; Sehgal, Shilpi; Bhatnagar, Shinjini; Pallavi, Kshetrapal; Sharma, Arundhati (Hormone and Metabolic Research, 2019)
The objective of the study is the functional characterization of a novel POU1F1 c.605delC mutation in combined pituitary hormone deficiency (CPHD) and to report the clinical and genetic details of 160 growth hormone deficiency patients. Screening of GH1, GHRHR, POU1F1, PROP1, and HESX1 genes by Sanger sequencing was carried out in 160 trios and 100 controls followed by characterization of the POU1F1 c.605delC mutation by expression studies including site directed mutagenesis, co-transfection, protein degradation, and luciferase assays to compare the wild type and mutant POU1F1. In vitro studies showed that the POU1F1 c.605delC mutation codes for a truncated protein with reduced transactivation capacity on its downstream effectors, viz., growth hormone (GH) and prolactin (PRL) causing severe CPHD. Experiments using different protease inhibitors reveal rescue of the protein upon blockage of the lysosomal pathway that might be useful in novel drug designing using targeted approach thereby maintaining the milieu and preventing/delaying the disease. The study provides an insight into the disease causing mechanism of POU1F1 c.605delC mutation identified in a CPHD child with severe short stature and failure to thrive. It also shows mutation effect on the expression, function and turnover of protein and highlights mechanistic details by which these potent regulators may operate.
Keywords: CPHD; POU1F1; mutation screening; mutation characterization